Phytotherapy of Gastric Ulcer (Literature Review) - Djanaev G.Yu; Askarov O.O; Sultanov S.A (Zien Journals, 2022)
Pharmacotherapy of diseases of the stomach and duodenum should be aimed at restoring and normalizing the interaction of acid-pepsin and gastroduodenal mucosa protectors in the gastric mucosa. Peptic ulcer disease is a common disease that affects millions of people and has a high recurrence rate. "No stomach acid, no ulcer" is a false assumption. Excessive secretion of gastric acid is only one factor in the pathogenesis of peptic ulcer disease. Their etiology is multifactorial, both offensive and defensive. It develops when the balance of its components is disturbed. Due to the limited efficacy and serious side effects of currently available drugs, its treatment faces great difficulties. Natural products such as plants and their isolated compounds have been widely used in experimental models of gastric ulcer. In these studies is a literature review of flavonoid-containing herbal plants showing ulcer activity in experimental models using different mechanisms of action
Keywords: gastric ulcer; pathogenesis; etiology; medicinal plants